IMPLEMENTASI SISTEM PELAYANAN PAJAK MODERN DI KANTOR PELAYANAN PAJAK PRATAMA BANJARBARU - Fauzan Fakhrurrohman; Fatimah (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
This study aims as a reference and evaluation of how the development of a modern tax service system that occurs in the Banjarbaru area, especially in the KPP Pratama Banjarbaru. The analytical technique used in this research is qualitative analysis, namely by describing the data that is already available. This study provides information about modern tax services that occur at the KPP Pratama Banjarbaru. This study will explain what are the positive and negative influences in the implementation of modern tax services for the community.